1998
DOI: 10.1007/s002210050512
|View full text |Cite
|
Sign up to set email alerts
|

Spatial disparity affects visual-auditory interactions in human sensorimotor processing

Abstract: Information from the auditory and visual systems converges in the nervous system with physiological and behavioral consequences. Most of our knowledge about the rules governing such convergence has been obtained in experiments where the strength or the timing of the individual auditory and visual stimuli has been varied. Relatively little attention has been paid to the spatial relationship between different modalities of stimuli in multisensory experiments. We studied saccadic reaction times of human subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 18 publications
9
73
0
Order By: Relevance
“…Note that to clearly illustrate this relationship, only 1 significant interaction per neuron is contained within this plot because spontaneous activity was invariant across conditions. Again, the relationship was most apparent in the log-log transformed plot and points were best fit to the power function y ϭ 38.152 x Ϫ0.3615 with an r 2 ϭ 0.3401. multisensory responses may speed the time to the initiation of premotor activity in the SC (Bell et al 2001), a result that fits nicely with observations of multisensory-mediated speeding of eye movements (Corneil and Munoz 1996;Frens and Van Opstal 1998;Frens et al 1995;Harrington and Peck 1998;Hughes et al 1994), the role of the different subpopulations of SC multisensory neurons to this effect remain to be determined. From a mechanistic perspective, the current study illustrates that fundamental features of a given neuron's response characteristics are strong determinants of multisensory integration.…”
Section: Introductionsupporting
confidence: 76%
“…Note that to clearly illustrate this relationship, only 1 significant interaction per neuron is contained within this plot because spontaneous activity was invariant across conditions. Again, the relationship was most apparent in the log-log transformed plot and points were best fit to the power function y ϭ 38.152 x Ϫ0.3615 with an r 2 ϭ 0.3401. multisensory responses may speed the time to the initiation of premotor activity in the SC (Bell et al 2001), a result that fits nicely with observations of multisensory-mediated speeding of eye movements (Corneil and Munoz 1996;Frens and Van Opstal 1998;Frens et al 1995;Harrington and Peck 1998;Hughes et al 1994), the role of the different subpopulations of SC multisensory neurons to this effect remain to be determined. From a mechanistic perspective, the current study illustrates that fundamental features of a given neuron's response characteristics are strong determinants of multisensory integration.…”
Section: Introductionsupporting
confidence: 76%
“…As such, cross-modal cues reinforce one another, increasing the likelihood of detecting and/or initiating an orienting response to the initiating event, as was repeatedly obtained in experiments with behaving cats (see Jiang et al 2002;Stein et al 1988Stein et al , 1989Wilkinson et al 1996). A host of studies with humans have demonstrated analogous perceptual and behavioral benefits from such multisensory cues (Bolognini et al 2004;Frassinetti et al 2002;Frens et al 1995;Goldring et al 1996;Harrington and Peck 1998;Laurienti et al 2004;Lovelace et al 2003). …”
Section: Discussionmentioning
confidence: 76%
“…As was mentioned above, due to the blocking of different stimulus conditions, our measures of RT enhancement effects must be considered to be conservative. In addition, it is well known that MRE decreases with increasing spatial disparity between the stimuli from different modalities (Colonius & Arndt, 2001;Frens, Van Opstal, & Van der Willigen, 1995;Harrington & Peck, 1998;Hughes, Nelson, & Aronchick, 1998;Spence & Driver, 1997a, 1997b. Due to limitations of our experimental setup, the stimuli from different modalities could not be presented at the same spatial location, possibly contributing to an underestimation of the true effect as well.…”
Section: Discussionmentioning
confidence: 96%